Court vs. Courtship in Jane Austen’s Emma - Mortuza, Shamsad (EAST WEST JOURNAL OF HUMANITIES, 2013)
The paper examines the royal dedication of Jane Austen’s Emma as a critical engagement with the regency crisis. Austen decided to comply with a royal request to dedicate Emma to the Prince Regent and inserted it almost as a last-minute adjustment, even though she had the option to include it in one of her future works. I shall argue that this inclusion of the dedication is far from an accident. While the novel’s preoccupation with marriage and courtship probably hides its courtly interest, the textual treatment of contextual foils and foibles, disease and decadence directly implicate the ‘regency crisis’. The paper adopts a new historicist approach and claims that Emma is an Austenite search for an ideal ruler at a time when the court was troubled by the deﬁciencies in the reigning monarch.